Pharmacokinetic assessment of isoniazid and acetylisoniazid in carbon tetrachloride-induced liver injury model in Wistar rats - Swati Sharma; Aishwarya Anand; Nipun Verma; Vishal Sharma; Alka Bhatia; Amol N Patil; Dibyajyoti Banerjee (Wolters Kluwer Medknow Publications, 2023)
Background: N-acetyl transferase 2 (NAT2) polymorphism testing could not see the light of success as a biomarker tool in tuberculosis management. Additionally, the antitubercular treatment (ATT) drug's reintroduction regimen variations exist because of the scarcity of robust preclinical evidence on ATT drug metabolism. Objective: The experiment was planned to understand the pharmacokinetic (PK) behavior of isoniazid and acetylisoniazid (AcINH) in a Wistar rat model of acute liver injury induced by carbon tetrachloride (CCl4) and preclinical drug-induced liver injury (DILI) model induced with CCl4 + anti-Tuberculosis (TB) drugs together. Materials and Methods: Thirty rats were used for the experiment and were divided into five groups. All rats were administered a single 0.5 ml/kg CCl4 intraperitoneal injection on day 0 to induce an animal model of DILI. Group I rats received CCl4 alone. Groups II-V were started on additional gavage feedings of isoniazid (H) alone, H plus rifampicin (R), H plus pyrazinamide (Z), and H, R, and Z together, respectively, daily for 21 days subsequently. Isoniazid and AcINH PK assessment was accomplished on day 20 of continuous once-daily dosing. Liver function test (LFT) monitoring was done at baseline on days 1, 7, and 21. On the last day of experiments, all experimental rats were sacrificed. Results: Three-week ATT administration sustained the CCl4-induced LFT changes. Area under the curve (AUC) values for isoniazid and AcINH were found to be 2.24 and 1.69 times higher in the H + R group compared with the CCl4 + H group, respectively (P < 0.05). Isoniazid and AcINH maximum concentration (Cmax) reached the highest, while isoniazid clearance reached the lowest in the H + R group. AcINH AUC increased by double in the CCl4 + Isoniazid+Rifampicin+Pyrazinamide (HRZ) group compared with the CCl4 + H group (P < 0.05). Biochemical, histological, and antioxidant changes were consistent with the new liver injury model's development. Conclusion: Rifampicin almost doubles up the isoniazid and AcINH exposure, in presence if DILI.